Model Klasifikasi Analisis Kepuasan Pengguna Perpustakaan Online Menggunakan K-Means dan Decission Tree - Khamim Surya Hadi Kusuma Al Atros; Abdul Robi Padri; Odi Nurdiawan; Ahmad Faqih; Saeful Anwar (STMIK Budi Darma, 2021)
Riyadlul Muta'allimin Elementary School Library is one of the support units in the school's academic activities. During times like these, students are very difficult in accessing the library in school. Therefore, the school applies an Online Library, so those students and teachers who can access the library do not need to flock to school. Online libraries that have been implemented need to do an evaluation of user satisfaction because this is a new thing for Riyadlul Muta'allimin Elementary School. Satisfaction analysis can be done by the K-Means method with a decision tree. K-Means is used to group data that will be converted into labels. It is further classified using a decision tree. Based on the analysis, the prediction of cluster 1 with true cluster 1 of 48 items, true cluster 0 and true cluster 0 there are no items, then the class precision is 100%